Disruption of Lateral Olivocochlear Neurons via a Dopaminergic Neurotoxin Depresses Sound-Evoked Auditory Nerve Activity - Le Prell, Colleen G. (Springer-Verlag, 2005)
We applied the dopaminergic (DA) neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) to the guinea pig cochlear perilymph. Immunolabeling of lateral olivocochlear (LOC) neurons using antibodies against synaptophysin was reduced after the MPTP treatment. In contrast, labeling of the medial olivocochlear innervation remained intact. As after brainstem lesions of the lateral superior olive (LSO), the site of origin of the LOC neurons, the main effect of disrupting LOC innervation of the cochlea via MPTP was a depression of the amplitude of the compound action potential (CAP). CAP amplitude depression was similar to that produced by LSO lesions. Latency of the N1 component of the CAP, and distortion product otoacoustic emission amplitude and adaptation were unchanged by the MPTP treatment. This technique for selectively lesioning descending LOC efferents provides a new opportunity for examining LOC modulation of afferent activity and behavioral measures of perception.